Similar patterns of clonally expanded somatic mtDNA mutations in the colon of heterozygous mtDNA mutator mice and ageing humans - Baines, Holly L. (Elsevier Science Ireland, 2014)
•Colonic crypts with mitochondrial dysfunction accumulate with age in PolgA+/mut mice.•Mitochondrial dysfunction is caused by clonally expanded mtDNA point mutations.•The mutations are random and their expansion is not subject to selective constraints.•Colonic crypts of aged humans have a similar mtDNA mutation spectrum and phenotype.•PolgA+/mut mice are a good model to study mitochondrial dysfunction in ageing colon.